Pengaruh Mobilisasi Dini Terhadap Peningkatan Peristaltik Usus Pada Pasien Post Operasi Di RSU Dr. Wahidin Sudiro Husodo Mojokerto - Nyunariani Puspita Sari (MEDICA MAJAPAHIT, 2013)
Postoperative, anesthesia given to patients will provide loss of normal peristalsis for 24 to 48 hours, depending on the type and duration of surgery because of anesthesia provides barriers to nerve stimuli for the occurrence of peristalsis so as to provide some effects such as abdominal distention (bloating or pain), even Paralytic ileus. One of the threatment that can be given to increase the intestinal peristalsis is to do mobilization. Design used in this research is Quasi Experiment, with the design of Non Equivalent Control Group. Variables independent variables Wet early mobilization and the dependent variable were intestinal peristalsis. Researchers used 30 respondents as a study sample, 15 respondents as the intervention group treated early mobilization and 15 respondents as a control group not treated early mobilization. data collection using observational methods. Sampling type wes quota sampling. The results showed that 15 respondents in the control group did not experience an intestinal peristalsis increasing. While in the experimental group, three respondents did not experience intestinal peristalsis increasing (<5x/menit) and 12 respondents experienced an increase in intestinal peristalsis (5-35 times / minute). In the experimental group, from observations obtained Peristaltic intestinal average 5.55 / min, median 5.55 x / minute, 5x/menit mode. In the control group, obtained an average of 1.43 / min, median 1x/menit, 0x/menit mode. From the above results that the mean disimplkan intestinal peristalsis in the experimental group is greater than the control group. Patients peristaltic bowel who performed early mobilization postoperative increased much faster than patients who did not performed early mobilization postoperative. With a proven research that early mobilization may enhance intestinal peristalsis in postoperative patients, nurses should pay more attention to early mobilization as an alternative intestinal peristaltic function in patients recovering postoperative